An Electronic Portfolio to Support Learning - Anne Wade; Philip Abrami; Jennifer Sclater (The Canadian Network for Innovation in Education (CNIE), 2005)
n this paper, we provide a description of a CSLP research project that looked at portfolio use within a middle school, the web-based e-portfolio software we have developed within the context of the Quebec educational system, our plans for further development of the tool, and our research plans related to the use of portfolios to support learning. Our aim is to combine research evidence on portfolio use with practical feedback from the field in an attempt to develop easy-to-use, powerful software designed to support active self-regulated student learning in schools.